2016
DOI: 10.1186/s12933-016-0467-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A enhances macrophage differentiation and lipid uptake in high glucose conditions: a cellular mechanism for accelerated macro vascular disease in diabetes mellitus

Abstract: BackgroundVascular disease in diabetes is initiated by monocyte adhesion to vascular endothelium, transmigration and formation of foam cells. Increasing clinical evidence supports a role for the secretory protein, cyclophilin A in diabetic vascular disease. The means by which cyclophilin A contributes to vascular lesion development in diabetes is however largely unknown.MethodsIn this study we investigated using THP1 cells and human monocytes whether cyclophilin A under hyperglycemic conditions, functions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…The contribution of HG to inflammatory processes was considered a major risk factor for the development of diabetes and cardiovascular complications . Studies have reported that HG‐induced oxidative stress elevated ROS and activated P2X7R, which were identified as activators of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of HG to inflammatory processes was considered a major risk factor for the development of diabetes and cardiovascular complications . Studies have reported that HG‐induced oxidative stress elevated ROS and activated P2X7R, which were identified as activators of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the downregulating effect played by FPP on CyPA gene expression, but not from the antioxidant control, may be of relevance, when considering that it has become clear that a hyperglicemia and oxidative stress milieu may stimulate this molecule [56] which, on its turn, drives the ox-LDL-mediated differentiation and activation of monocytes to foam cells [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of atherogenesis, Seizer et al reported that eCypA promoted the differentiation of CD34+ progenitor cells into foam cells via CD147, thereby contributing to the progression of atherosclerosis 51 . Likewise, Ramachandran et al reported that eCypA enhanced macrophage lipid uptake and foam cell formation 52 . In addition, Liu et al reported in human patients that high plasma CypA was correlated with progressive peripheral arterial occlusion disease (n=68) and impaired renal function in chronic renal disease 53 .…”
Section: Pathological Roles Of Extracellular and Intracellular Cyclopmentioning
confidence: 98%